Evaluation of peri-implant bone levels and soft tissue dimensions around zirconia implants-a three-year follow-up study - Kniha, Kim; Schlegel, K. A.; Kniha, H.; Modabber, A.; Hoelzle, F. (International Journal of Oral & Maxillofacial Implants, 2018)
The aim of this study was to measure bone levels around zirconia implants during follow-up of up to 3 years. Additionally, the effect of clinical contact point positions on the papilla deficit was evaluated. Eighty-one patients with 105 zirconia implants were examined at the 3-year follow-up. Bone levels were measured on the date of implant placement and at 3 months, 1year, and 3 years thereafter. Distances between the first bone-implant contact and the contact point of the crowns and between the bone level at the adjacent tooth and the contact point of the crowns were assessed. The effect of the clinical contact point position on the papilla deficit was also assessed. Significant reductions in the distances between the bone-implant contact and the implant shoulder, as well as the contact point of the crowns, and between the bone level at the adjacent tooth and the contact point of the crowns, were found. A significant association was found between the papilla deficit and the height of the contact point. Implant survival was 100% and implant success was 95.4%. While zirconia implants presented little bone loss up to 1year, significant bone apposition was observed up to 3years. Low contact points correlated with full papillae, whereas high contact points were associated with a papilla deficit.
EVALuna2:34228

Papilla-Crown Height Dimensions around Zirconium Dioxide Implants in the Esthetic Area: A 3-Year Follow-Up Study - Kniha, Kim; Schlegel, Karl Andreas; Kniha, Heinz; Modabber, Ali; Neukam, Friedrich Wilhelm; Kniha, Kristian (Journal of Prosthodontics, 2019)
Purpose Soft tissue interactions with ceramic dental implants have previously been shown to have favorable esthetic outcomes. This study aimed to evaluate the papilla-crown proportion around zirconia implants in a 3-year follow-up study and the correlation between the gingival biotype and changes in papillary height. Materials and Methods This was a prospective study of 39 patients with 40 single-gap implants (Straumann PURE Ceramic ZLA Implant). The papilla-crown proportion was assessed after 3 months, 1 year, and 3 years. In addition, correlations between the peri-implant biotypes and changes in papillary heights were evaluated. Results The papilla-crown proportion improved from 35.5% after 3 months to 41.7% after 3 years. The gingival biotype was correlated very weakly to papilla height alterations. Significant papillary fill was observed in the interdental space between 3 months and 3 years (p < 0.001). Conclusions An ideal papilla-crown proportion of 40% around single implants was observed after 3 years. A thin or thick gingival biotype showed a very weak correlation with soft tissue alterations.
CRIS-Team WoS Importer:2019-03-06

Peri-implant changes in papillary dimensions around zirconium dioxide implants in the esthetic area - Kniha, Kristian; Schlegel, Karl Andreas; Kniha, Heinz; Hoelzle, Frank; Modabber, Ali; Kniha, Kim (Implantologie, 2018)
The study aimed to evaluate the papilla-crown proportion around zirconia implants in a 3-year follow-up study. In addition, the correlation between the gingival biotype and changes in papillary height were evaluated. This was a prospective study of 39 patients with 40 single-gap implants assessing the papilla-crown proportion after 3 months, 1 year, and 3 years. Furthermore, correlations between the peri-implant biotypes and changes in papillary heights were evaluated. The papilla-crown proportion improved from 35.5% after 3 months to 41.7% after 3 years. Significant papillary fill was observed in the interdental space between 3 months and 3 years (P < .001). The gingival biotype had a moderate correlation to papilla height alterations. A thin or thick gingival biotype presented a very weak correlation with papilla height alterations (Spearman's rho = -0.57)
EVALuna2:35696